Investigations of the Coastal Part of Ilyich-1 Settlement in 2015–2016 - Sharov, Oleg (Hyperboreus, 2019)
A survey of the excavations of the coastal part of Ilyich-1 Settlement conducted by the expedition of the Institute for the History of Material Culture (IHMC) in 2015–2016.